Simple fly fishing : techniques for tenkara and rod & reel - Chouinard, Yvon, 1938- (Patagonia Books, 2014)
Modern-day fly fishing, like much in life, has become exceedingly complex, with high-tech gear, a confusing array of flies and terminal tackle, accompanied by high-priced fishing guides. This book reveals that the best way to catch trout is simply, with a rod and a fly and not much else. It teaches the reader how to discover where the fish are, at what depth, and what they are feeding on. Then it describes the techniques needed to present a fly at that depth, make it look lifelike, and hook the fish. In chapters on wet flies, nymphs, and dry flies, its authors employ both the tenkara rod as well as regular fly fishing gear to cover all the bases. With paintings by renowned artist James Prosek, technical illustrations, and inspiring photographs and stories throughout, Simple Fly Fishing reveals the secrets and the soul of this captivating sport.--Publisher.